2011
DOI: 10.1007/s00122-011-1718-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of quantitative disease resistance to southern leaf blight and of multiple disease resistance in maize, using near-isogenic lines

Abstract: Maize inbred lines NC292 and NC330 were derived by repeated backcrossing of an elite source of southern leaf blight (SLB) resistance (NC250P) to the SLB-susceptible line B73, with selection for SLB resistance among and within backcross families at each generation. Consequently, while B73 is very SLB susceptible, its sister lines NC292 and NC330 are both SLB resistant. Previously, we identified the 12 introgressions from NC250P that differentiate NC292 and NC330 from B73. The goals of this study were to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
6
41
0
Order By: Relevance
“…In contrast to the largely upstream mechanisms (i.e., perception and signaling) described above for moderate-to-large effect loci, studies on quantitative resistance of predominantly small-effect loci in maize suggested that the majority of potential causal genes affected downstream resistance mechanisms (Kump et al, 2011;Belcher et al, 2012) (Figure 2). The predominant class of genes linked to these loci as potential causal genes were those involved in downstream defense mechanisms including defensins, pathogenesis-related proteins, and secondary metabolite enzymes.…”
Section: Relationship Of Allelic Effect Size and Molecular Function Imentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to the largely upstream mechanisms (i.e., perception and signaling) described above for moderate-to-large effect loci, studies on quantitative resistance of predominantly small-effect loci in maize suggested that the majority of potential causal genes affected downstream resistance mechanisms (Kump et al, 2011;Belcher et al, 2012) (Figure 2). The predominant class of genes linked to these loci as potential causal genes were those involved in downstream defense mechanisms including defensins, pathogenesis-related proteins, and secondary metabolite enzymes.…”
Section: Relationship Of Allelic Effect Size and Molecular Function Imentioning
confidence: 96%
“…The 5000-line maize NAM population has been applied to the study of quantitative resistance for a number of pathogens, including southern leaf blight, and these studies are beginning to illuminate a recurring pattern of resistance loci (Kump et al, 2011;Belcher et al, 2012). This analysis identified a minimum of 32 quantitative trait loci (QTLs) using a single pathogen isolate.…”
Section: Polygenic Architecture Of Quantitative Resistancementioning
confidence: 99%
“…Generally, those alleles identified effects that were quantitative and additive in action and contributed only a small amount of resistance (Balint-Kurti and Carson, 2006;, 2007a, 2008aBelcher et al, 2012;Carson et al, 2004;Kump et al, 2011;Negeri et al, 2011;Pengfei, 2011;Zwonitzer et al, 2009). Generally, those alleles identified effects that were quantitative and additive in action and contributed only a small amount of resistance (Balint-Kurti and Carson, 2006;, 2007a, 2008aBelcher et al, 2012;Carson et al, 2004;Kump et al, 2011;Negeri et al, 2011;Pengfei, 2011;Zwonitzer et al, 2009).…”
mentioning
confidence: 99%
“…Previous studies in maize have provided some evidence for the presence of MDR alleles (Belcher et al, 2012;Wisser et al, 2011;Zwonitzer et al, 2010). Multiple disease resistance alleles, that is, alleles that confer resistance to two or more diseases, are of great interest to breeders.…”
mentioning
confidence: 99%
“…At the chromosomal segment level, disease and insect resistance loci colocalize in a nonrandom fashion (McMullen and Simcox 1995;Williams 2003;Wisser et al 2005) and loci have been identified that confer resistance to diverse pathogen isolates and taxa (Zwonitzer et al 2010;Chung et al 2011;Belcher et al 2012). There is evidence to suggest that gene clusters can confer resistance to more than one disease.…”
mentioning
confidence: 99%